Руки моей не отпускай: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Эксмо, 2019)
Экземпляры: ЦБ (20191004) / Инвентарный номер: 51364 / Цена: 187.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-44